Microwave planar filter topologies based on ring resonators with coupled-lines combination / Sameh Kh M Khanfar - M Khanfar, Sameh Kh (2015)
Microwave planar filter topologies based on ring resonators with coupled-lines combination / Sameh Kh M Khanfar